PH‐Responsive Porous Nanocapsules for Controlled Release. Issue 1 (4th December 2017) - Song, Jun; Wei, Yanlong; Hu, Jiwen; Liu, Guojun; Huang, Zhengzhu; Lin, Shudong; Liu, Feng; Mo, Yangmiao; Tu, Yuanyuan; Ou, Ming
Abstract: In this work pH‐responsive porous nanocapsules have been successfully prepared from a ternary graft copolymer, poly(glycidyl methacrylate)‐ g ‐[poly(2‐cinnamoyloxyethyl methacrylate)‐ r ‐poly(ethylene glycol) methyl ether‐ r ‐poly(2‐diethylaminoethyl methacrylate)] or PGMA‐ g ‐(PCEMA‐ r ‐MPEG‐ r ‐PDEAEMA). The graft copolymers were fabricated by grafting three types of polymer chains onto the backbone polymer by using click chemistry. These ternary copolymers underwent self‐assembly to form vesicles in a DMF/water solvent mixture. While the MPEG chains served as the corona and stabilized the vesicles, the vesicle wall was composed of a dominant PCEMA continuous phase that was interspersed by PDEAEMA domains. After photo‐cross‐linking, the PDEAEMA domains were embedded in the structurally locked PCEMA wall. By decreasing the pH of the external solution, we were able to trigger the release of encapsulated pyrene due to the capsule wall becoming porous as a result of the PDEAEMA chains bearing positively charged amine groups stretching into the water. While these pH‐responsive porous nanocapsules exhibited potential applications in drug delivery, detection and catalysis, the strategy reported in this contribution also represented a new paradigm for the design and preparation of other novel stimuli‐responsive porous nanocapsules. Abstract : Gated delivery : pH‐Responsive porous nanocapsules have been prepared from ternary graft copolymers and used as potential vehicles for controlled release of drugs, food, and bioactive compounds (see figure).